PERAN DUKUNGAN SUPERVISI MEMODERASI PENGARUH KARAKTERISTIK PEKERJAAN DAN TEAM WORK TERHADAP KINERJA KARYAWAN DI PT. E-T-A INDONESIA - Novida Talib Sanad; Muhadjir Anwar (ITB AAS Indonesia Surakarta, 2023)
The data presented by the Badan Pusat Statistik (BPS) shows that Indonesia cannot be separated from the impact of the pandemic which can affect the quality of employment. This can be seen from the August 2020 Index Kinerja Pekerja (IKP) of 43.78, a decrease of 20.7% from 55.23 in August 2019. Performance appraisal data at PT E-T-A Indonesia has changed downward with a trend from 2019 to 2022 .With project assessment components, departmental targets, individual competencies and discipline. This study aims to (1) determine the relationship between job characteristics and PT E-T-A Indonesia employee performance, (2) determine the relationship between Team Work and PT E-T-A Indonesia employee performance, (3) the role of supervisor support to moderate the effect of job characteristics on performance. employees of PT E-T-A Indonesia, (4) the supervisor support role relationship moderates the effect of Team Work on the performance of employees of PT E-T-A Indonesia. The population of this study were permanent employees of PT E-T-A Indonesia with a total sample of 75 respondents. The data used is primary data through distributing questionnaires to respondents. The analysis was performed using the Partial Least Square (PLS) method using SmartPLS version 3 software. The results of the study concluded that (1) Job Characteristics can contribute to improving employee performance, (2) Team Work can contribute to improving employee performance, (3) Supervision support is proven to be a moderating variable for the influence of Job Characteristics on Employee Performance, and (4) Supervision support is not proven as a moderating variable for the influence of Team Work on Employee Performance.